Pengaruh Jenis Formula Media Pembawa dan Bakteri PGPR (Plant Growth Promoting Rhizobacteria) Dalam Memacu Pertumbuhan dan Menekan Penyakit Blas (Blast) pada Tanaman Padi Beras Merah Lokal Jatiluwih - NABABAN, TRIWANTO; SUDANA, I MADE; SINGARSA, I DEWA PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
The Effect of PGPR (Plant Growth Promoting Rhizobacteria) Bacteria Carier Media Formulas in Growth S timulate and Suppressing The Presece of Blast Diseases in Jatiluwih Local Brown Rice Plants. This study aims to determine the effect of PGPR (Plant Growth Promoting Rhizobacteria) bacteria carier media Formulas in growth stimulate and suppressing the presece of blast diseases in jatiluwih local brown rice plants. Formulas will be tested directly in the field to determine the best formula to stimulate growth and suppress blast disease in local brown rice jatiluwih. The formulas tested were sand, flour, liquid PPG, compost and control which was given 1% mixture of PGPR bacteria 4 kinds of rhizobacteria, namely Serratia marcescens, Achromobacter spanius, Providencia vermicola, Myroldes adoratimimis. 1 clump of seeds immersed in the formula for 24 hours then sowing in the field. each treatment repeated 5 times. The planting pattern in this study used a randomized block design (RBD) and observed variables ranging from growth to yield. All data obtained were analyzed quantitatively using analysis of variance (ANOVA) at the 5% level. The results showed that all treatments using the formulas could stimulate the growth and resistance of brown rice plants to blast disease then the yield of brown rice plants could be increased. Liquid PPG and rhizobacteria PGPR formulas that have better capabilities than other formulas.